Mitochondrial genome characterization and phylogenetic analysis of Blastocladiella sp. (Blastocladiales: Blastocladiaceae) - Xu Wang; Na Liu (Mitochondrial DNA. Part B. Resources, 2020)
In the present study, the complete mitochondrial genome of an early diverging fungus Blastocladiella sp. was assembled by the next-generation sequencing. The complete mitochondrial genome of Blastocladiella sp. is 33, 800 bp in length and consists of 11,620 (34.38%) adenine, 5,047 (14.93%) cytosine, 6,025 (17.83%) guanosine and 11,108 (32.86%) thymine. The genome contains 19 protein-coding genes, 24 tRNA genes and 2 rRNA genes. Phylogenetic analysis based on the combined mitochondrial gene set showed that Blastocladiella sp. has a close relationship with Allomyces macrogynus and Blastocladiella emersonii.